ERGOTHERAPY IN RESTORING THE FUNCTIONAL ACTIVITY OF WOMEN AGED 50–60 WITH NEGLECT AFTER A STROKE - Pozmogova, N. V.; Bogdanovska, N. V.; Kalonova, I. V. (Rehabilitation and Recreation, 2024)
Cognitive impairment after stroke is common, but remains underdiagnosed and complicates the prognosis of recovery. Some forms of cognitive impairment are observed in 40–70% of patients. The work is devoted to the specifics of the recovery of people after a stroke, against the background of which the unilateral visual-spatial ignoring syndrome, or the neglect syndrome, developed. A theoretical review of the scientific literature on this issue is presented, as well as an evaluation of the effectiveness of the program of occupational therapy intervention with the use of mirror therapy and elements of the Perfetti method in restoring the functional activity of patients with the consequences of a stroke in the conditions of a neurological hospital. The emphasis in the proposed neuropsychological rehabilitation program is on the timely diagnosis of the neglect syndrome, the early start of rehabilitation measures, the ease of application of the technique, which does not require special expensive equipment, the possibility of participation and interaction in the correctional and restorative work of both specialists who work with the patient and his immediate environment. On the basis of a set of studies, which included a theoretical analysis of scientific and methodological literature, analysis of medical documentation, determination of indicators of functional capabilities of the upper limb according to the Sollerman test and stereognosis according to the Moberg test, assessment of the patient’s functional independence according to FIM, as well as mathematical statistics methods, the effectiveness of the combination of mirror therapy was proven and elements of the Perfetti technique, which accelerates the recovery of motor function in patients with cognitive impairment after a right-hemisphere ischemic stroke in the acute and early recovery periods. Mirror therapy was carried out starting from the early recovery period, as soon as the patient’s general condition allowed, that is, hemodynamic parameters were stable and the patient could be verticalized. Training with elements of the Perfetti technique was carried out using special simulators. With the help of the Perfetti technique, the patient received the opportunity to re-evaluate information from his own body. The method allows you to learn to feel your body, distinguish the position of body parts.